Insultos verbais no cotidiano de Salvador (1889-1908): filho de negra captiva e outros nomes que o respeito manda calar - Santos, Eneida Virginia de Oliveira (2015)
In Bahia the process of social and political rearrangement derived from the end of slavery and implementation of the Republic was marked by inequality around the color in order to maintain unchanged the existing social order. In the color differentiation processes, the press was instrumental in settling lower values on the black-mestizo population, displaying in sessions police's subjects images and behavior also "incorrect". These images fulfilled two functions: educating popular on the ideal role models and honor to be practiced and inform the police about the subjects that should be corrected. But not only the ruling classes built the color difference. Popular from Salvador, in the period between the last years of the nineteenth and first decade of the twentieth century in conflicts around work, neighborhood and business, built color meaning that differed from its rivals and expressed them in the form of insults verbal. In this work we identify the meanings attributed the color contained in the vocabulary of insults uttered by ordinary people on the streets of the city. People that different from ones that the press insisted on reform because the public display of incivility in the form of conflict to knife, shot or clubbed, leaned against the law to restore its reputation.